A Robust Nonprecious CuFe Composite as a Highly Efficient Bifunctional Catalyst for Overall Electrochemical Water Splitting. Issue 2 (25th November 2019) - Inamdar, Akbar I.; Chavan, Harish S.; Hou, Bo; Lee, Chi Ho; Lee, Sang Uck; Cha, SeungNam; Kim, Hyungsang; Im, Hyunsik
Abstract: To generate hydrogen, which is a clean energy carrier, a combination of electrolysis and renewable energy sources is desirable. In particular, for both the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in electrolysis, it is necessary to develop nonprecious, efficient, and durable catalysts. A robust nonprecious copper–iron (CuFe) bimetallic composite is reported that can be used as a highly efficient bifunctional catalyst for overall water splitting in an alkaline medium. The catalyst exhibits outstanding OER and HER activity, and very low OER and HER overpotentials (218 and 158 mV, respectively) are necessary to attain a current density of 10 mA cm −2 . When used in a two‐electrode water electrolyzer system for overall water splitting, it not only achieves high durability (even at a very high current density of 100 mA cm −2 ) but also reduces the potential required to split water into oxygen and hydrogen at 10 mA cm −2 to 1.64 V for 100 h of continuous operation. Abstract : A facile, scalable, nonprecious, and robust copper–iron (CuFe) bimetallic composite is demonstrated as highly‐efficient and durable bifunctional catalyst for overall water splitting. It exhibits outstanding oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) activities, requiring very low overpotentials of 218 and 158 mV respectively. It also exhibits low cell voltage of 1.64 V to generate a current density of 10 mA cm −2 in 1 m KOH electrolyte.